A consensus on outcome measures for device-based interventions that seek to restore bilateral and binaural hearing in adults with single-sided deafness - Katiri, Roulla (2023)
Objectives: Unilateral severe-to-profound sensorineural hearing loss (single-sided deafness, SSD) often has functional, psychological, and social consequences. Interventions for adults with SSD include hearing aids and auditory implants. Benefits and harms of these interventions (outcome domains) are until now reported inconsistently in clinical trials involving adults with SSD. Inconsistency in reporting of outcome measures prevents meaningful comparisons or syntheses of trial results. The Core Rehabilitation Outcome Set for Single Sided Deafness (CROSSSD) international initiative used structured communication techniques to achieve consensus among healthcare users and professionals working in the field of SSD. The product is a set of core outcome domains that experts agree are critically important to assess in all clinical trials of SSD interventions. An assessment of the available measurement instruments for relevance and comprehensiveness has implications on how the outcome domains should be measured in clinical trials assessing the benefits and harms of SSD interventions.